Refeudalisation Revisited: The Destruction of Deliberative Democracy. Issue 1 (3rd April 2018) - Murdock, Graham
Abstract : Donald Trump's election as American President and the successful referendum campaign to exit the EU in Britain have prompted renewed interest in the challenges posed to deliberative democracy by right-wing populism. This paper returns to the research on authoritarianism developed by the Frankfurt School in Germany and the United States, and particularly to their emphasis on the performative construction of appeals, and to Jurgen Habermas's later characterisation of the translation of citizens into spectating subjects as a refeudalisation of the public sphere, and argues that these analyses continue to provide indispensable resources for understanding contemporary developments.